Radiative casson fluid over a slippery vertical riga plate with viscous dissipation and buoyancy effects / Siti Khuzaimah Soid ... [et al.] - Soid, Siti Khuzaimah; Abdul Hamid, Khadijah; Nasero, Ma Nuramalina; Abdul Aziz, NurNajahNabila (2021)
The application of Casson fluid such as concentrated fruit juice and tomato sauce might involve problems during the manufacturing process to maintain their high quality. This study aims to investigate the radiative Casson fluid in the presence of the magnetic field, velocity slip, thermal slip, viscous dissipation and buoyancy effects over permeable slippery vertical Riga stretching and shrinking plates. The governing partial differential equations are translated into ordinary differential equations using similarity transformation. The equations are then solved numerically using a boundary value problem solver (BVP4C) in MATLAB software. The skin friction coefficient and the heat transfer rate are significantly influenced by the Casson fluid and the modified Hartmann number which both coefficients increase for stretching and shrinking plates. Concurrently, their fluid flows increase while heat distributions decrease in the boundary layer for both plates. This theoretical research becomes a benchmark for the food industry especially in producing canned food.